The Role of Aqidah Akhlak Teachers in Improving Social Media Morals According to Islamic Teachings at MTsS Plus Al-Amin Lembang - Yulianti; Iwarjah, Yupantri; Yulistianingsih; Yunus; Yusniati (MANDAILING GLOBAL EDUKASIA, 2024)
The development of technology and social media has a major influence on student behavior in interacting in the digital world. Ease of access to information is often not balanced with a good understanding of ethics, resulting in various problems, such as the spread of hoaxes, hate speech, and online bullying. Therefore, the role of Akidah Akhlak teachers is very important in guiding students to use social media in accordance with Islamic teachings. This study aims to analyze the role of Akidah Akhlak teachers in improving social media morals at MTsS Plus Al-Amin Lembang. The method used is qualitative research with a descriptive approach. Data were collected through interviews, observations, and documentation. The results of the study show that Akidah Akhlak teachers play a role in instilling Islamic values ​​through character education, ethical habits in the use of social media, and providing role models in attitudes and behavior. Teachers apply lecture methods, discussions, and personal guidance as the main strategies in improving students' understanding of social media ethics. With guidance from Akidah Akhlak teachers, students are expected to be able to use social media more wisely, responsibly, and make it a useful tool in accordance with Islamic principles